The gingerbread man - Aylesworth, Jim.; McClintock, Barbara (New York : Scholastic Press, 1998)
A freshly baked gingerbread man escapes when he is taken out of the oven and eludes a number of pursuers until he meets a clever fox.
450
Accelerated Reader AR
Keywords: Fairy tales; Folklore -- Juvenile literature